Travel vaccination mapping application (VacMAP) - Goh, Chun Yi (Nanyang Technological University, 2021)
Before COVID-19 sweeps across the world, people were mindful over the vaccinations that they are required to take before they travel to certain countries. However, most travellers are unsure on what are all the recommended vaccinations imposed by the destination countries, and the additional vaccinations they would need to take before travelling, based on their existing vaccination records. In the current COVID-19 situation, it is even more integral that people are aware of the recommended vaccines, e.g. covid-19 vaccine, before travelling to other countries. This process would inevitably become a norm in future travel planning. Currently, Singapore still lacks a ‘one stop’ application that provides the information of the additional vaccinations recommended to be taken by the travellers before their travel, based on their existing vaccination records. Hence, by creating a web-based solution for travel vaccines and immunisation management, people will be able to enter their own immunisation records in the website and be informed of the recommended vaccines that they are lacking in before their travel. This will undeniably smoother the process when planning for an overseas travel.